Arterial spin labeling perfusion magnetic resonance imaging of non-human primates - Zhang, Xiaodong; Li, Chun-Xia (Quantitative Imaging in Medicine and Surgery, 2016)
Non-human primates (NHPs) resemble most aspects of humans in brain physiology and anatomy and are excellent animal models for translational research in neuroscience, biomedical research and pharmaceutical development. Cerebral blood flow (CBF) offers essential physiological information of the brain to examine the abnormal functionality in NHP models with cerebral vascular diseases and neurological disorders or dementia. Arterial spin labeling (ASL) perfusion MRI techniques allow for high temporal and spatial CBF measurement and are intensively used in studies of animals and humans. In this article, current high-resolution ASL perfusion MRI techniques for quantitative evaluation of brain physiology and function in NHPs are described and their applications and limitation are discussed as well.